Using host-guest interactions at the interface of quantum dots to load drug molecules for biocompatible, safe, and effective chemo-photodynamic therapy against cancer - Wu Xiaoxia; Yang Jinghui; Xing Jie; Lyu Yonglei; Zou Ruifen; Wang Xin; Yao Junlie; Zhang Dinghu; Qi Dawei; Shao Guoliang; Wu Aiguo; Li Jianwei (ROYAL SOC CHEMISTRY, 2025)
Combining photodynamic therapy (PDT) and chemotherapy (CHT) by loading an anti-cancer drug and a photosensitizer (PS) into the same delivery nanosystem has been proposed as an effective approach to achieve synergistic effects for a safe cancer treatment. However, exploring an ideal delivery nanosystem has been challenging, because the noncovalent interactions must be maintained between the multiple components to produce a stable yet responsive nanostructure that takes into account the encapsulation of drug molecules. We addressed this issue by engineering the interfacial interaction between Ag2S quantum dots (QDs) using a pillararene derivative to direct the co-self-assembly of the entire system. The high surface area-to-volume ratio of the Ag2S QDs provided ample hydrophobic space to accommodate the anti-drug molecule doxrubicine. Moreover, Ag2S QDs served as PSs triggered by 808 nm near-infrared (NIR) light and also as carriers for high-efficiency delivery of drug molecules to the tumor site. Drug release experiments showed smart drug release under the acidic microenvironments (pH 5.5) in tumor cells. Additionally, the Ag2S QDs demonstrated outstanding PDT ability under NIR light, as confirmed by extracellular and intracellular reactive oxygen species generation. Significant treatment efficacy of the chemo-photodynamic synergistic therapy for cancer using the co-delivery system was demonstrated via in vitro and in vivo studies. These findings suggest that our system offers intelligent control of CHT and PDT, which will provide a promising strategy for constructing hybrid systems with synergistic effects for advanced applications in biomedicine, catalysis, and optoelectronics.